Aquaporins as Biomarkers for Pancreatic Cancer - Fonseca, Elisabete Sofia Antunes Dias Nobre (2022)
By 2030, pancreatic cancer is anticipated to overtake lung cancer as the second leading cause of cancer-related death. Surgery is now the primary treatment option for treating pancreatic cancer, but it’s crucial to remember that only a very small proportion of patients have a resectable tumour at the time of diagnosis. An early pancreatic cancer diagnosis is still difficult due to the absence of distinguishing symptoms and distinct clinical indications. Aquaporins (AQPs) are a family of water channel proteins. Their function of facilitating water and glycerol, among other solutes, has been linked to carcinogenesis while being overexpressed in various cancer types. Therefore, aquaporins’ expression has been associated with tumour cell motility, tumour proliferation, and the potential for metastasis. Several signalling pathways, including JNK/ERK/p38 MAPK, P13K/AKT/mTOR, and Wnt/β-catenin, growth factors, and even epithelial-mesenchymal transition, are also correlated to the activity and regulation of AQPs. The global aim of this work is to determine aquaporins’ expression in pancreatic cancer, their interplay with pathways involved in tumorigenesis and to validate aquaporins as possible prognosis and/or diagnosis biomarkers in pancreatic cancer. 25-paired healthy and tumour pancreatic tissues in different stages of differentiation were analysed by real-time quantitative polymerase chain reaction for relative expression of aquaporin-1 (AQP1), aquaporin-3 (AQP3), aquaporin-5 (AQP5), aquaporin-9 (AQP9), e-cadherin (Ecad), vimentin (Vim), epidermal growth factor receptor (EGFR), extracellular signal-regulated protein kinase-1 (ERK1), extracellular signal-regulated protein kinase-2 (ERK2), proto-oncogene Jun (c-Jun), and proto-oncogene Fos (c-Fos), both transcription factors subunits of activator protein 1 (AP-1). These results were analised according to variables such as age, gender, invasiveness grade, and aggressiveness grade. Aquaporins’ mRNA was detected in both healthy and tumour tissues. Ecad and Vim mRNA levels were higher in high-invasive grade tumours in female patients. ERK1 mRNA level was increased in low-invasive grade tumours from male patients. c-Jun and AQP3 were both overexpressed in low-invasive grade tumours. AQP3 and AQP9 correlated positively with c-Jun in tumour tissues, while AQP5 correlated with EGFR and Ecad. AQP9 was for the first time detected in pancreatic healthy and tumour tissue. AQP3 has been identified as a possible biomarker for the invasiveness grade. This aquaporin is also correlated in tumour tissues with c-Jun, stating a possible involvement in cell proliferation and cell survival. AQP3 and AQP9 are directly involved in JNK MAPK pathway, while AQP5 may be indirectly involved in ERK MAPK pathway and epithelial-mesenchymal transition.»